Impetiginized Dyshidrotic Eczema - Tchernev, Georgi (Open Access Maced J Med Sci, 2017)
A 16 years old female patient, affected by atopic dermatitis and rhinoconjunctivitis allergica since childhood, requested a dermatologic consultation for lesions which had appeared after 3 months of local treatment with clobethasole propionate. The histological analysis confirmed the diagnosis of dyshidrotic eczema and the microbiological smears demonstrated a significant infection with Staphylococcus aureus. The risk of developing corticosteroids’ side-effects depends on the potency of the product, extended period of use and the volume of product applied. Clobetasol propionate is a group I- highly potent corticosteroid, which should be used for a maximum period of 2 weeks. Several authors have found that this agent has cumulative depot effect, persisting in the epidermis for 4 days after only one application. Taking together these observations, sustained by the clinical case presented above, we can conclude that the infectious risks associated with topical corticosteroid treatment must not be neglected, particularly since treated patients are fragile, and frequently have multiple well-known risk factors.